Comprehensive Analysis of CD4+ T Cell Responses to CMV pp65 Antigen Restricted by Single HLA-DR, -DQ, and -DP Allotype Within an Individual - Hyun, You-Seok; Jo, Hyeong-A; Lee, Yong-Hun; Kim, Sun-Mi; Baek, In-Cheol; Sohn, Hyun-Jung; Cho, Hyun-Il; Kim, Tai-Gyu (Frontiers in Immunology, 2021)
Within an individual, six different HLA class II heterodimers are expressed co-dominantly by two alleles of HLA-DR, -DQ, and -DP loci. However, it remained unclear which HLA allotypes were used in T cell responses to a given antigen. For the measurement of the CD4+ T cell responses restricted by a single HLA allotype, we established a panel of artificial antigen-presenting cells (aAPCs) expressing each single HLA allele of 20 HLA-DRB1, 16 HLA-DQ, and 13 HLA-DP alleles. CD4+ T cell responses to cytomegalovirus (CMV) pp65 restricted by single HLA class II allotype defined in 45 healthy volunteers. The average magnitude of CD4+ T cell responses by HLA-DR allotypes was higher than HLA-DQ and HLA-DP allotypes. CD4+ T cell responses by DRA*01:01/DRB1*04:06, DQA1*01:02/DQB1*06:02, DPA1*02:02/DPB1*05:01 were higher among the other alleles in each HLA-DR, -DQ, and -DP locus. Interestingly, the frequencies of HLA-DR alleles and the positivity of specific allotypes showed an inverse correlation. One allotype within individuals is dominantly used in CD4+ T cell response in 49% of donors, and two allotypes showed that in 7% of donors, and any positive response was detected in 44% of donors. Even if one individual had several dominant alleles, CD4+ T cell responses tended to be responded by only one of them. Furthermore, CD8+ and CD4+ T cell responses by HLA class I and class II were correlated. Our results demonstrate that the CD4+ T cell immune response to pp65 preferentially uses a few dominant HLA class II allotypes within individuals similar to HLA class I.